Inhibition of sodium‐linked glucose reabsorption normalizes diabetes‐induced glomerular hyperfiltration in conscious adenosine A1‐receptor deficient mice. (27th August 2013) - Sällström, J.; Eriksson, T.; Fredholm, B. B.; Persson, A. E. G.; Palm, F.
Abstract Aim Glomerular hyperfiltration is commonly observed in diabetics early after the onset of the disease and predicts the progression of nephropathy. Sustained hyperglycaemia is also closely associated with kidney hypertrophy and increased electrolyte and glucose reabsorption in the proximal tubule. In this study, we investigated the role of the increased tubular sodium/glucose cotransport for diabetes‐induced glomerular hyperfiltration. To eliminate any potential confounding effect of the tubuloglomerular feedback (TGF) mechanism, we used adenosine A1‐receptor deficient (A1AR−/−) mice known to lack a functional TGF mechanism and compared the results to corresponding wild‐type animals (A1AR+/+). Methods Diabetes was induced by an intravenous bolus injection of alloxan. Glomerular filtration rate (GFR) was determined in conscious mice by a single bolus injection of inulin. The sodium/glucose cotransporters were inhibited by phlorizin 30 min prior to GFR measurements. Results Normoglycaemic animals had a similar GFR independent of genotype (A1AR+/+ 233 ± 11 vs. A1AR−/− 241 ± 25 μL min−1), and induction of diabetes resulted in glomerular hyperfiltration in both groups (A1AR+/+ 380 ± 25 vs. A1AR−/− 336 ± 35 μL min−1; both P < 0.05). Phlorizin had no effect on GFR in normoglycaemic mice, whereas it reduced GFR in both genotypes during diabetes (A1AR+/+ 365 ± 18 to 295 ± 19, A1AR−/− 354 ± 38 to 199 ± 15 μL min−1; both P < 0.05). Notably, the reduction was more pronounced in the A1AR−/− (P < 0.05). Conclusion This study demonstrates that increased tubular sodium/glucose reabsorption is important for diabetes‐induced hyperfiltration, and that the TGF mechanism is not involved in these alterations, but rather functions to reduce any deviations from a new set‐point.